GGOS tropospheric delay forecast product performance evaluation and its application in real-time PPP. (October 2018) - Yao, Yibin; Xu, Xingyu; Xu, Chaoqian; Peng, Wenjie; Wan, Yangyang
Abstract: Tropospheric delay is one of the main error sources in Global Navigation Satellite System (GNSS) precise positioning, as the GNSS signal is influenced by refraction when travelling through the troposphere. Generally, tropospheric delay is estimated as a parameter in GNSS data processing. With the increasing demand for GNSS real-time applications, high-precision tropospheric delay augmentation information is essential to enhance convergence speed and precision of positioning. The Global Geodetic Observing System (GGOS) Atmosphere provides total zenith tropospheric delay (ZTD) forecast grid data, globally, one day in advance, where the time resolution is 6 h and spatial resolution is 2.5° × 2°. Here, the GGOS ZTD forecast product is assessed compared with ZTD information from global IGS sites, including an analysis of the spatial and temporal distribution of its error and the weather influence on its precision. Ultimately, the application effect of the GGOS Atmosphere ZTD forecast product in real-time precise point positioning (PPP) is examined. The results show that the positioning precision and the speed of convergence are obviously advanced, especially in the U direction, which informs the potential for real-time application of GGOS forecast products. Highlights: Performance of GGOS tropospheric delay forecasting products is evaluated. The temporal and spatial characteristics of product precision are distinct. A spherical harmonic model for systematic difference between ZTD models is proposed. GGOS forecast ZTD help accelerate PPP convergence, well-applied in GNSS positioning.